The mechanical coupling effect of laser shock and shot peening in Ti–6Al–4V dovetail joint: Residual stress, microstructure and fretting fatigue behavior - Chen Wang; Xiong Zhang; Yan Yin; Weifeng He; Yibo Shang; Liucheng Zhou (Journal of Materials Research and Technology)
This research systematically investigates the strengthening effects of laser shock peening (LSP), shot peening (SP), and combined LSP + SP on the fretting fatigue behavior of Ti–6Al–4V dovetail joints under different load levels. Multi-scale characterization reveals that all treatments generate gradient, heterogeneous grain structures and compressive residual stress (CRS), with LSP + SP producing the most significant surface CRS (673 MPa) and micro-hardness (377 HV0.3). Crucially, LSP + SP achieves the deepest grain refinement layer (420 μm), exceeding that of single SP or LSP (120 μm) by 3.5 times. Fretting fatigue tests reveal load dependent improvements: at higher loads (10 kN, 12 kN), LSP + SP yields the greatest life extension (7.08 and 4.57 times), while at lower loads (8 kN), SP offers the highest enhancement (8.71 times). Microstructural analysis indicates that LSP + SP transforms multi-crack initiation into single-source fracture and deepens crack origins from 70 μm to 663 μm, consistent with the refinement zone. Dense low angle grain boundaries (LAGBs) and dislocations near cracks slow early crack propagation. The enhanced fatigue performance results from the combined effects of microstructure and CRS, where surface CRS mainly influences crack initiation at low loads, whereas CRS penetration depth controls early crack growth at high loads. Overall, these findings show that LSP + SP effectively enhances damage tolerance by optimizing the interaction between subsurface stress and microstructure.